Incidental capture of seabirds in Argentinean side-haul trawlers - Tamini, Leandro Luis (2021)
Between April 2008 and July 2015, we conducted a total of 18 trips on five different side-haul trawlers fishing within the Argentine Exclusive Economic Zone, monitoring 486 hauls. We observed 100% of the hauls and monitored trawl cables for 136.7 hours, about 5% of the trawl effort, to identify the levels of seabird bycatch from net entanglements and collisions with trawl cables. A total of 35 net entanglements of White-chinned Petrels Procellaria aequinoctialis, Great Shearwaters Ardenna gravis, Black-browed Albatrosses Thalassarche melanophris and Southern Royal Albatross Diomedea epomophora were recorded, all of which occurred during the autumn and winter. Additionally, 656 seabird collisions against trawl cables were recorded including 39 heavy, 96 medium and 521 light. Further, we recorded nine Black-browed Albatrosses and two Great Shearwaters potentially dead. Although in the study fishery the number of deaths in the trawl cables could surpass the number of birds incidentally killed in nets, the mortality rate caused by the latter type of interaction far exceeds those observed in nets from other trawl fisheries operating in the Patagonian Shelf. Fortunately, 26% of the seabirds entangled in the net were recovered and released alive, which indicates that awareness and training in safe bird handling and release may improve captured seabird survival rates. The main objectives of this work is to highlight a little-studied source of seabird mortality by entanglement, to generate discussion on potential technical mitigation measures for side-haul trawl fisheries, and to propose crew training in safe handling and release of seabirds as an immediate mitigation measure.